SIGNIFICANCE OF Treg CELLS FOR ADENOSINE-MEDIATED IMMUNE SUPPRESSION IN COLORECTAL CANCER - G. A. Zhulai; E. K. Oleinik; A. V. Churov; A. A. Romanov; P. N. Kravchenko (Semakova); V. M. Оleinik (Медицинская иммунология, 2017)
At the present time, immunosuppressive role of extracellular adenosine in carcinogenesis is actively investigated. Colorectal cancer is one of the most common types of malignant neoplasms in Russia and worldwide, but the role of mediators of adenosine-dependent immunosuppression, such as CD39 (that hydrolyze ATP to adenosine), CD73, A2AR, is not yet clear in patients with colorectal cancer. The levels of specific mRNAs for A2AR, ectonucleotidase CD39, and CD73 genes were assayed in white blood cells of the patients with colorectal cancer. The results have shown that the CD39 mRNA content is increased in the patients with colorectal cancer in the course of the disease progression. Meanwhile, no significant difference for CD73 gene expression was found between the patients and healthy donors. Moreover, an increase in A2AR mRNA expression was noted for the patients with advanced colorectal cancer, thus presuming potential activation of adenosine-A2AR-mediated immunosuppressive mechanism. Furthermore, the CD39 expression on T cells was elevated in parallel to the cancer progression. The most significant changes in CD39 expression were observed for both T helper and Treg cell populations at the late stages of colorectal cancer. Similarly, a direct correlation was revealed between CD39 expression on CD4+CD25+CD127lo/-Treg cells, and changes of A2AR mRNA levels in leukocytes from the cancer patients.